The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00701-006-1082-0
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injuries: the impact of early intervention on late sequelae. A randomized controlled trial

Abstract: In this particular MTBI sample, early active rehabilitation did not change the outcome to a statistically-significant degree. Further studies should focus on patients with several complaints during the first 1-3 months and test various types of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 42 publications
1
75
1
1
Order By: Relevance
“…Many either failed to use a randomized clinical trial (RCT) or controlled trial without randomizing (Goranson, Graves, Allison, & La Freniers, 2003;Gronwall, 1986;Minderhoud, Boelens, Huizenga, & Saan, 1980), or failed to state the process of randomization when used (Ghaffar, McCullagh, Ouchterlony, & Feinstein, 2006;Rath, Simon, Langenbahn, Sherr, & Diller, 2003). Only two studies (Tiersky et al, 2005;Elgmark Andersson, Emanuelson, Bjorklund, & Stalhammer, 2007) explained a process for concealing group allocation, and only three studies reported blind outcomes measurement (Elgmark Andersson et al, 2007;Leonard, 2004;Tiersky et al, 2005).…”
Section: Internal Validitymentioning
confidence: 99%
“…Many either failed to use a randomized clinical trial (RCT) or controlled trial without randomizing (Goranson, Graves, Allison, & La Freniers, 2003;Gronwall, 1986;Minderhoud, Boelens, Huizenga, & Saan, 1980), or failed to state the process of randomization when used (Ghaffar, McCullagh, Ouchterlony, & Feinstein, 2006;Rath, Simon, Langenbahn, Sherr, & Diller, 2003). Only two studies (Tiersky et al, 2005;Elgmark Andersson, Emanuelson, Bjorklund, & Stalhammer, 2007) explained a process for concealing group allocation, and only three studies reported blind outcomes measurement (Elgmark Andersson et al, 2007;Leonard, 2004;Tiersky et al, 2005).…”
Section: Internal Validitymentioning
confidence: 99%
“…However, a program started from two to eight weeks by a qualified rehabilitation team, for TBI patients, did not prove the difference between an early start and a rehabilitation start after one year from injury, because the patients analyzed in this study did not report improvement of sequelae, thus generating controversy in the investigations [10][11][12] (B).…”
Section: Recommendationmentioning
confidence: 83%
“…Given the frequency with which OEF/OIF veterans meet screening criteria for probable brain injury, a substantial number of individuals are likely to suffer from the unrecognized and untreated consequences of TBI. At present, little empirical evidence exists to document the effectiveness of interventions for mild brain injury (Elgmark Andersson et al, 2007;Ghaffar et al, 2006;Paniak et al, 2000). The challenge of developing and conducting rigorous evaluation of treatments for mild brain injury presents an important opportunity to help OEF/OIF veterans.…”
Section: Discussionmentioning
confidence: 99%